Peroxymonosulfate/LaCoO3 system for tetracycline degradation: Performance and effects of co-existing inorganic anions and natural organic matter. (October 2021) - Yang, Xue; Wu, Puqiu; Chu, Wei; Wei, Gaoling
Abstract: The activation of peroxymonosulfate (PMS) has been developed as an efficient method for the degradation of antibiotics by generating reactive oxygen species (ROS), where perovskite oxides have been found as effective catalysts. However, the reaction mechanism, degradation pathways, as well as the effects of co-existing inorganic anions and natural organic matter are largely unknown. Therefore, the degradation efficiency and mechanism of tetracycline (TC) through the activation of PMS by LaCoO3 were investigated. Moreover, the effects of common inorganic anions and natural organic matter (e.g., humic acid (HA)) on degradation efficiency were also compared. Without the presence of coexisting substance, TC removal exceeded 90% within 30 min, while 72% mineralization was achieved in 6 h, under optimal reaction conditions at neutral pH. In addition to the traditional free radicals of OH and SO4 −, 1 O2 and O2 − also contributed the degradation process, where the lattice oxygen of LaCoO3 played a significant role in 1 O2 production. The degradation of TC followed the pathways including demethylation, hydroxylation and ring-opening reactions. The presence of inorganic anions (i.e., H2 PO4 −, Cl − and SO4 2− ) and low-concentration of HA promoted the degradation. Among them, H2 PO4 − and lower concentration of HA showed the most obvious outcome, while the SO4 2− can regulate the radical formation, minimize the peak radical level, and therefore promote the overall performance of the process. LaCoO3 exhibited stable reusability with minor decrease in TC removal, likely due to the adsorption of intermediate products from previous stages. These obtained results shed light on the application of perovskite oxides for PMS activation on removing antibiotics. Highlights: A novel and recyclable catalyst of LaCoO3 is used to degrade tetracycline with PMS. The LCO/PMS was efficient in the removal and mineralization of Tetracycline. The reaction mechanism was studied with the impact of OH, SO4 −, 1 O2 and O2 − . Influence of SO4 2−, NO3 −, Cl −, H2 PO4 − and humic acid in water were all investigated.